Infrared monitoring of the metal surface temperature of superheater pipes in transient modes - A. A. Valke; V. A. Zakharenko; D. G. Lobov; D. B. Ponomarev; A. G. Shkaev; M. Yu. Nikolaev; S. V. Lukuta (Омский научный вестник)
This work is devoted to the problem of infrared monitoring of the metal temperature of the surface of superheater pipes. Monitoring is implemented on the basis of a thermal imager cameras that performs contactless monitoring of the surface temperature of the pipes of the wall superheater. The results of modeling the temperature distribution along the pipe of a wall-mounted superheater in the presence of contamination and without are presented. The calculation of the number of thermal imager cameras required for infrared monitoring is performed. The developed design solutions for the installation site of thermal imager cameras on a TP-82 type boiler have been confirmed experimentally.